2019
DOI: 10.1007/s10828-019-09108-7
|View full text |Cite
|
Sign up to set email alerts
|

The loss of feminine gender in Norwegian: a dialect comparison

Abstract: It is well known that grammatical gender systems may change historically. Previous research has documented loss of the feminine gender in several Norwegian dialects, including those spoken in Oslo and Tromsø (Lødrup 2011; Rodina and Westergaard 2015a). In these dialects, the change is characterized by substitution of the feminine indefinite article ei (e.g., ei bok 'a book') with the masculine form en (e.g., en bok). Child and adult native speakers of the Trondheim dialect (N=71) participated in two production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 21 publications
(32 reference statements)
2
20
0
1
Order By: Relevance
“…This test was solely included to make sure that our participants actually matched the expected production profile as described in available dialect grammars (e.g., Mæhlum and Røyneland, 2012 ). This was of special relevance since, as mentioned in section 2.2, the gender system is currently changing in many dialects, and previous studies have shown that the change has proceeded surprisingly rapidly in the Bokmål areas in and around Trondheim and Tromsø (Busterud et al, in press ; Rodina and Westergaard, 2015 ). The production test was administered by a speaker of the local dialect to encourage the speakers to speak the local dialect.…”
Section: Participantsmentioning
confidence: 86%
See 1 more Smart Citation
“…This test was solely included to make sure that our participants actually matched the expected production profile as described in available dialect grammars (e.g., Mæhlum and Røyneland, 2012 ). This was of special relevance since, as mentioned in section 2.2, the gender system is currently changing in many dialects, and previous studies have shown that the change has proceeded surprisingly rapidly in the Bokmål areas in and around Trondheim and Tromsø (Busterud et al, in press ; Rodina and Westergaard, 2015 ). The production test was administered by a speaker of the local dialect to encourage the speakers to speak the local dialect.…”
Section: Participantsmentioning
confidence: 86%
“…The new system that is arising in the bigger cities Oslo, Trondheim and Tromsø thus has the conservative Bokmål indefinite paradigm, and the popular Bokmål definite paradigm. However, there are tendencies both in Oslo (see below) and Trondheim (Busterud et al, in press ) to also replace the feminine definite suffix with a general masculine/common gender suffix.…”
Section: Introductionmentioning
confidence: 99%
“…Masculine is without doubt the morphological default in Norwegian, with feminine being the most vulnerable gender. In many dialects, feminine is disappearing and is being replaced by masculine ( Lødrup, 2011 ; Rodina and Westergaard, 2015 ; Busterud et al, forthcoming ). It is conceivable that the role of masculine in heritage Russian is strengthened under the influence of Norwegian, a language with a strong masculine default.…”
Section: Discussionmentioning
confidence: 99%
“…For example, traditional Norwegian grammars (such as Faarlund et al 1997) consider the definite suffix to be an exponent of gender (see also Andersson 2000 and Dahl 2000 for a similar conclusion for Swedish). On the other hand, applying the definition given by Hockett (1958), which states that "[g]enders are classes of nouns reflected in the behavior of associated words" (see also Corbett 1991), this suffix should not be considered to be an exponent of gender, but rather a declension class marker, as argued in Fretheim 1985, Lødrup 2011, Rodina & Westergaard 2015, Lohndal & Westergaard 2016, Svenonius 2017, and Busterud et al 2019. An in-between position is pursued by Enger (2004a:137), who argues that the suffix encodes gender to a certain degree (see also Berg 2019).…”
Section: Theoretical Assumptions and Research Questionsmentioning
confidence: 99%
“…Grammatical gender is acquired relatively late in Norwegian, due to the nontransparency of gender assignment (Rodina & Westergaard 2013). A surprising finding in recent years is that feminine gender appears to be in the process of being lost in many dialects of Norwegian, including areas where the traditional three-gender system has been assumed to be quite stable in the spoken language, such as Tromsø (Rodina & Westergaard 2015) and Trondheim (Busterud et al 2019). Studies of Scandinavian heritage languages also show that the grammatical gender system is somewhat vulnerable in these populations (Heegård Petersen & Kühl 2017 for Heritage Danish, Larsson 2015 andWestergaard 2016 for Heritage Norwegian).…”
Section: Introductionmentioning
confidence: 99%